1997
DOI: 10.1029/97gl01403
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of HNO3 with water‐ice surfaces at temperatures of the free troposphere

Abstract: Abstract. The uptake of gas-phase HNO3 by water-ice films has been measured in a low-temperature, coated-wall flow tube under conditions where water-ice, and not a hydrate of nitric acid, is thermodynamically stable. It is observed that there-is uptake of HNO3 on the order of l•3x10 TM molecules per cm 2 of ice film on a short timescale, and a somewhat smaller uptake on a much longer timescale of 10's of minutes. The short timescale uptake is insensitive to the nitric acid partial pressure, varying by not more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
279
3
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(305 citation statements)
references
References 19 publications
21
279
3
2
Order By: Relevance
“…However, it is only recently that the first quantitative studies of the scavenging ability of ice under tropospheric conditions were performed, by observing the loss of gas phase nitric acid onto thin films formed either by freezing liquid water [Abbatt, 1997] •Now at Department of Chemistry, University of Chicago, Chicago, IL, 60637.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is only recently that the first quantitative studies of the scavenging ability of ice under tropospheric conditions were performed, by observing the loss of gas phase nitric acid onto thin films formed either by freezing liquid water [Abbatt, 1997] •Now at Department of Chemistry, University of Chicago, Chicago, IL, 60637.…”
Section: Introductionmentioning
confidence: 99%
“…When a snowflake grows in the atmosphere, or precipitates, it can absorb gases, aerosols, and supercooled droplets (Colbeck, 1981;Abbatt, 1997;Kuhn, 2001;Hoog et al, 2007). The large surface area of snowflakes leads to an efficient scavenging and removal of atmospheric pollutants (Chang, 1984;Barrie, 1991;Lei and Wania, 2004), which then end up in the snow cover.…”
Section: Introductionmentioning
confidence: 99%
“…Dominé and Thibert [52] suggested that HNO 3 is incorporated in ice growing by deposition of layers of a given thickness whose composition is determined by condensation kinetics. Solid diffusion is not a viable explanation for the large uptake of HNO 3 , due to its low diffusion coefficient and solubility in ice [69].…”
Section: Nomentioning
confidence: 99%